A review on dill essential oil and its chief compounds as natural biocide. (6th November 2020) - Kaur, Vishaldeep; Kaur, Ramandeep; Bhardwaj, Urvashi
Abstract: Anethum graveolens L. (dill), a member of Umbelliferae family, is an important essential oil‐bearing herb native to the Mediterranean and West Asia. It is well documented for its medicinal and traditional uses. The chemical composition of dill seed essential oil showed the presence of numerous volatile compounds with carvone, limonene, α‐phellandrene, β‐phellandrene and p‐cymene being the major ones in almost all its aerial parts. Thus, the main focus of this updated review is to highlight the biological importance of dill essential oil and its major constituents (carvone and limonene) reported till date. Although the number of reviews has been published on its chemical composition and medicinal uses, its role in the field of agriculture to develop commercial formulations is still needed to be explored. In brief, the information presented in this review will be useful in creating interest in the use of dill essential oil and its major constituents for the development of commercial plant‐based pesticides. Abstract : Dill plant, major constituents of essential oil from its different parts and their biological activities.